1952
DOI: 10.1002/jez.1401190303
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ocular growth and differentiation of clusters of mouse embryonic shields cultured with and without primitive endoderm and in the presence of possible inductors

Abstract: , Y a r y l a n d EIGHT FIGURESLittle is known of the mechanisms of primary organization in mammalian embryos, largely because of technical difficulties in dealing with the early stages in. utero. A number of important problems can be approached (Nicholas, '47), however, by use of the techniques of explantation and transplantation, both separately and in combination. In earlier reports (Grobstein, '50b, '51) it was shown that individual mouse embryonic shields, separated from trophoblast and the remainder of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1952
1952
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The developmental competence of the mouse embryo's native pluripotent cells has been studied extensively in classical studies using heterotopic grafting (Grobstein 1951(Grobstein , 1952 and in situ labeling (Lawson et al 1991). In those studies, postimplantation embryonic epiblast never developed into TB derivatives.…”
Section: D8 R M Roberts and Othersmentioning
confidence: 99%
“…The developmental competence of the mouse embryo's native pluripotent cells has been studied extensively in classical studies using heterotopic grafting (Grobstein 1951(Grobstein , 1952 and in situ labeling (Lawson et al 1991). In those studies, postimplantation embryonic epiblast never developed into TB derivatives.…”
Section: D8 R M Roberts and Othersmentioning
confidence: 99%
“…We should like to comment on the remarkable structural similarity of apical organization in proximal endoderm cells of stages as early as days 6-8 of embryogenesis with the typical architecture of absorptive cells of distal regions of the small intestine, prominently ileum, of neonatal rats. Our results suggest that (i) proximal endoderm cells are highly differentiated in their ultrastucture [see also 42, 661, (ii) special features of epithelial cells of the neonatal ileum are already established very early in foetal life and (iii) the proximal endoderm before primitive streak formation may represent precursor cells to the definitive ileum of the small intestine, unlike other definitive endodermal cells of the foetus which are widely believed to be derived from embryonic ectoderm [compare 42, [67][68][69]. From numerous studies on processes of protein uptake and intracellular distribution in the intestine of newly born mammals it has been concluded that the 'apical endocytic complex' and its associated particle-covered membranes are engaged in protein absorption and endocytotic uptake, apparently in a rather non-selective mode [53-55,581. In the same studies a role in protein or particle storage, perhaps with some lysosome-like degradative activity, has been suggested for the large supranuclear vacuoles of ileal cells of newborn mammals [53][54][55]58,70,71].…”
Section: Discassionmentioning
confidence: 99%